2017
DOI: 10.1111/ap.12248
|View full text |Cite
|
Sign up to set email alerts
|

Excellence in Research in Australia 2010, 2012, and 2015: The Rising of the Curate's Soufflé?

Abstract: Objective: The Excellence in Research for Australia (ERA) data collections completed in 2010, 2012, and 2015 were developed by the Australian Research Council to identify the quality of research produced by the broad range of Australian tertiary education institutions. In each evaluation, the quality of research produced by the institutions was rated on a 5-point scale ranging from "well above world standard" to "well below world standard" within each field of research (FoR). The FoRs relevant to psychology i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Overall examination of the data showed that a number of AOUs have undergone changes in ranking (i.e., as indicated by performance on 17, then 1701, 1702, and 1799 as ranked in that order of selection; see Table ) from the 2015 to 2018 data collection. The serially based ranking of the scoring criteria was the same as that used in the previous studies (Crowe & Samartgis, ; Crowe & Watt, ), as it was considered that each measured a unique, although correlated, aspect of the ratings of the respective Universities. Thus, a 17 score of 5, a 1701 score of 5 and a 1702 score of 4, for example, was considered to demonstrate greater strength and diversity of ratings than was a score of 5 on both 17 and 1,701 alone, thus, culminating in a higher ranking.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall examination of the data showed that a number of AOUs have undergone changes in ranking (i.e., as indicated by performance on 17, then 1701, 1702, and 1799 as ranked in that order of selection; see Table ) from the 2015 to 2018 data collection. The serially based ranking of the scoring criteria was the same as that used in the previous studies (Crowe & Samartgis, ; Crowe & Watt, ), as it was considered that each measured a unique, although correlated, aspect of the ratings of the respective Universities. Thus, a 17 score of 5, a 1701 score of 5 and a 1702 score of 4, for example, was considered to demonstrate greater strength and diversity of ratings than was a score of 5 on both 17 and 1,701 alone, thus, culminating in a higher ranking.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis was undertaken to update the findings of the two previous studies (Crowe & Samartgis, ; Crowe & Watt, ) which examined the ERA data in psychology from 2010 to 2012 and from 2012 to 2015. The analysis of all four ERA exercises indicates that: Journal articles are the principal area of production with a number of journal articles in psychology doubling from 2010 to 2018. There has been a stepwise increase in research income, commercialisation income, and staffing numbers across the four data collections. For code 17 in 2010, 34% of the institutions were rated at or above world standard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, are the results of a project designed to gauge the quality of the nation's research effort called the Excellence in Research for Australia assessment (ERA) initiated by the Australian Research Council (ARC). Dealing with the 2 years 2010 and 2012, the conclusion insofar as psychology was concerned was that is was “like the Curate's egg…good in parts” (Crowe & Samartgis, ), followed by a modest improvement by 2015 (Crowe & Witt, ).…”
Section: Mainstream Psychologymentioning
confidence: 99%
“…In the article by Crowe and Watt (2016), the ratings of 41 -Australian universities across the years 2010, 2012, and 2015 were evaluated for the psychology codes used as part of the Excellence in Research in Australia (ERA) data collections. Overall, performance was maintained or improved across the targeted years; although as Crowe and Watt highlight, it is of concern that 39% of the institutions included in the analyses failed to meet the benchmark of world standards.…”
mentioning
confidence: 99%